Beliefs and Practices of Three Literacy Instructors in Elementary Teacher Education - Courtland, Mary Clare; Leslie, Laurie (Alberta Journal of Educational Research, 2010)
This article describes the beliefs and practices of three literacy teacher educators at one site of a longitudinal multisite case study of teacher education and literacy teaching that describes teacher candidates’ experiences in literacy courses and their first two years of literacy teaching. One instructor held a social constructivist perspective and focused on depth of conceptual understanding; two promoted breadth to prepare the students for the early years of teaching. The courses highlighted print literacy. Neither critical literacy, multiliteracies, or multimodality were emphasized. Instructors perceived that their students were prepared to teach literacy, but noted inconsistencies between their courses and practices in the field experience.